Costunolide-Induced Apoptosis via Promoting the Reactive Oxygen Species and Inhibiting AKT/GSK3β Pathway and Activating Autophagy in Gastric Cancer - Xu, Cuixiang; Huang, Xiaoyan; Lei, Xiaohua; Jin, Zhankui; Wu, Min; Liu, Xiao; Huang, Yubin; Zhao, Xiangrong; Xiong, Yue; Sun, Jingying; Duan, Xianglong; Wang, Jianhua (Frontiers in Cell and Developmental Biology, 2021)
Objective: Costunolide (Cos) is a sesquiterpene lactone extracted from chicory. Although it possesses anti-tumor effects, the underlying molecular mechanism against gastric cancer cells remains unclear. This study aimed to explore the effect and potential mechanism of Cos on gastric cancer. Methods: The effect of Cos on HGC-27 and SNU-1 proliferation was detected by CCK-8 and clone formation assay. The changes in cell apoptosis were determined using Hoechst 33258 and tunel staining. The morphology of autophagy was analyzed by autophagosomes with the electron microscope and LC3-immunofluorescence with the confocal microscope. The related protein levels of the cell cycle, apoptosis, autophagy and AKT/GSK3β pathway were determined by Western blot. The anti-tumor activity of Cos was evaluated by subcutaneously xenotransplanting HGC-27 into Balb/c nude mice. The Ki67 and P-AKT levels were examined by immunohistochemistry. Results: Cos significantly inhibited HGC-27 and SNU-1 growth and induced cell cycle arrest in the G2/M phase. Cos activated intrinsic apoptosis and autophagy through promoting cellular reactive oxygen species (ROS) levels and inhibiting the ROS-AKT/GSK3β signaling pathway. Moreover, preincubating gastric carcinoma cells with 3-methyladenine (3-MA), a cell-autophagy inhibitor, significantly alleviated the effects of Cos in inducing cell apoptosis. Conclusion: Cos induced apoptosis of gastric carcinoma cells via promoting ROS and inhibiting AKT/GSK3β pathway and activating pro-death cell autophagy, which may be an effective strategy to treat gastric cancer.